Age and gender stratified normative values for the International Prostate Symptom Score for adults aged 60 years and over. Issue 8 (21st June 2018) - Booth, Lorna; Skelton, Dawn A.; Hagen, Suzanne; Booth, Joanne
Abstract : Aims: To identify age and gender stratified normative values for the International Prostate Symptom Score (IPSS) for older community‐living adults. Methods: Secondary analysis of data from a large cohort study produced norms presented as means, standard deviations, medians, ranges, and percentile scores. Non‐parametric analyses were conducted to investigate the effect that demographic variables, smoking status and comorbidity had on the severity of Lower Urinary Tract Symptoms (LUTS) as measured by the IPSS. Results: Data from a total of 1103 survey respondents of community‐living men and women aged between 60 and 99 years in the UK were analyzed. Normal ranges for the IPSS (as indicated by the median and 25th to 75th percentiles) were within the mild and low moderate LUTS categories of the IPSS, irrespective of age or gender. Age, gender, co‐habitant status, and comorbidity had an effect on LUTS severity with comorbidity being the best predictor of IPSS scores. Conclusion: This study has provided IPSS normative values for an older UK adult population aged 60‐99 years. These normative values can be used by researchers and practitioners for peer comparison making the individual's IPSS score more meaningful. Presenting the normative values suggests that some mild symptoms may be described as "normal." It may also help to combat the perception that poor bladder health is an inevitable part of aging, as all norms in the current study fell into either mild or low moderate symptom categories.